ANALISIS PERTIMBANGAN AGAMA DALAM HUKUM PERGANTIAN KELAMIN: (STUDI PUTUSAN MA No 177/Pdt.P/2021/PN Gpr dan No. 64/Pdt.P/2021/PN Bms) - Khodijah Nur Tsalis; Aullia Vivi Yulianingrum (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
Allah SWT created humans in two types: male and female. But sometimes, in the process of fetal growth in the stomach of pregnant women, things can happen that can interfere with fetal development and cause the fetus to be born in a state that looks like it has multiple sexes, or in medical terms, it is called Ambiguous Genitalia. As health technology advances, a person born with this condition can make repairs or refinements to his genitals after a series of medical examinations are carried out to determine which sex can be perfectly owned according to his biological and psychological conditions. In Indonesia, several similar cases led to changes in gender and names in population data. This can be done after there is a decision from the local District Court that ratifies and justifies the genital surgery that has been carried out. In the absence of a law that regulates the regulation of sex change, the judge is obliged to explore and understand the legal, customary, and religious values of the applicant. So to what extent do judges use religious considerations in deciding the application submitted in the case of sex change? This type of research is called library research because it uses library materials as the main data source. The results of this study indicate that although there is no specific law governing the regulation of sex change, judges are still obliged to make decisions by following the values and legal norms that apply in society. The judges of the Kediri and Banyumas District Courts have handled sex change cases committed by someone who was born with ambiguous genitalia. In granting the petition, the two judges, in addition to using legal and medical considerations, also used religious considerations, but in different petitions or petitions. The judge of the Banyumas District Court, in confirming or denying the purpose of the sex surgery, carried out religious considerations by quoting the MUI Fatwa. Meanwhile, the Judge of the Kediri District Court carried out religious considerations in the application for a name change by quoting the hadith of the Prophet Muhammad.